Three-dimensional simulation of granular materials by discrete element method (DEM) by considering the fracture effect of particles (Journal of Civil Engineering Researchers, 2023)
Coarse-grained materials, such as sand and gravel, exhibit a significant dependence on particle failure rate, which greatly influences their engineering behavior. This research focuses on the three-dimensional modeling of grain material behavior using the discrete element method (DEM) with PFC3D software and FISH programming language. The specific objective is to model the particle breakage phenomenon and its impact on resistance behavior and deformation. To accurately represent the non-spherical shape of the particles, an interconnected sphere approach was employed. The modeling of grain failure was achieved by establishing a failure criterion that considers two critical conditions: the heterogeneity of contact forces and stress within the particle. The proposed model and criteria were validated through comparison with triaxial experimental results obtained from the Purulia dam gravel. The results demonstrate that the developed model successfully captures the essential aspects of particle failure and its influence on the behavior of the granular environment. The simulations accurately represent the resistance behavior and deformation characteristics observed in the triaxial experiments. This validates the effectiveness of the proposed model in simulating the significant effects of particle failure on the behavior of coarse-grained materials. The findings of this study contribute to a deeper understanding of the complex behavior of coarse-grained materials, particularly in terms of their response to particle failure. The developed DEM model, incorporating the particle breakage phenomenon, provides a valuable tool for accurately predicting and analyzing the behavior of granular materials in various engineering applications.
Keywords: discrete component method; fracture effect; three-dimensional simulation; granular materials